Influences of the Work Environment on Nurses’ Psychological Wellbeing at Selected Teaching Hospitals in Lusaka, Zambia: A Focus on Secondary Traumatic Stress and Burnout - Kanyanta, Michael Mumba; Kabinga-Makukula, Marjorie; Wahila, Ruth (International Journal of Scientific Research and Management (IJSRM), 2025)
Introduction: The current study sought to establish associations of the nurse work environment, with Secondary Traumatic Stress and Burnout among nurses at selected Teaching Hospitals in Lusaka, Zambia.Methods: A correlational study was conducted at three Teaching Hospitals in Lusaka, Zambia using a stratified sample of 250 nurses. Spearman rank order correlations and hierarchical linear regression were employed to determine correlations among variables at 95% confidence level and 0.05 level of significance.Results:  Secondary Traumatic Stress was positively correlated with levels of nursing workload (rs = .18, p